The olfactory receptor OR51E2 activates ERK1/2 through the Golgi-localized Gβγ-PI3Kγ-ARF1 pathway in prostate cancer cells - Xu, Xin; Khater, Mostafa; Wu, Guangyu (Frontiers in Pharmacology, 2022)
The olfactory receptor OR51E2 is ectopically expressed in prostate tissues and regulates prostate cancer (PCa) progression, but its function and regulation in oncogenic mitogen-activate protein kinase (MAPK) activation are poorly defined. Here we demonstrate that -ionone, an OR51E2 agonist, dose-dependently activates extracellular signal-regulated kinases 1 and 2 (ERK1/2) in PCa cells, with an EC50 value of approximate 20 M and an efficiency comparable to other receptor agonists. We also find that CRISPR-Cas9-mediated knockout of Golgi-translocating G9 subunit, phosphoinositide 3-kinase  (PI3K) and the small GTPase ADP-ribosylation factor 1 (ARF1), as well as pharmacological inhibition of G, PI3K and Golgi-localized ARF1 activation, each abolishes ERK1/2 activation by -ionone. We further show that -ionone significantly promotes ARF1 translocation to the Golgi and activates ARF1 that can be inhibited by G9 and PI3K depletion. Collectively, our data demonstrate that OR51E2 activates ERK1/2 through the G-PI3K-ARF1 pathway that occurs spatially at the Golgi, and also provide important insights into MAPK hyper-activation in PCa.